Synthesis and swelling behaviour of oil palm empty fruit bunch based superabsorbent polymer composite - Norhazwani, Mat Sudin (2012)
Polyacrylicamide-graft-oil palm Empty Fruit Bunch (PAM-g-EFB) SAP was synthesized using graft copolymerization method of acrylicamide (AM) monomer onto EFB backbone with ammonium persulphate (APS) as an initiator and N’N’-methylenebisacrylamide (MBA) as cross-linker to assist the process. Determination of water absorbency was tested using tea bag method after immersed in distilled water. The effects on amount of initiator, cross-linker and filler towards water absorbency were studied to determine the optimum condition of EFB-g-PAM SAP. The maximum water absorbency was 263g/g, 223g/g and 250g/g when the optimum condition for initiator (APS), crosslinker (MBA) and filler (EFB) were at 10wt%, respectively. The characterization of the EFB-g-PAM SAP was characterized by FTIR spectroscopy while thermal stability was indicate using TGA.